PROFIL KEMAMPUAN PENALARAN MATEMATIS SISWA DALAM MENYELESAIKAN SOAL CERITA PERBANDINGAN DITINJAU DARI GAYA BELAJAR - Vatma Gelita Ta’uke; Alfisyahra; Nurhayadi; Anggraini (Universitas Nias Raya, 2026)
This study aims to profile the mathematical reasoning ability of grade VIID students of SMPK Bala Selamat Palu in solving comparative story problems reviewed from the learning style. The mathematical reasoning skills in question include proposing conjectures, mathematical manipulation, compiling evidence and giving reasons, and giving conclusions. This study uses a descriptive qualitative approach, with research subjects selected based on the results of the learning style questionnaire and recommendations from the subject teachers and then classified into three categories of learning styles: visual, auditorial, kinesthetic. Data collection was carried out through written tests and interviews. The data analysis in this study is in the form of condensation (data condensation), data display (data presentation), and conclusion drawing/verification (drawing conclusions and verification). The results showed that students with visual learning styles were able to meet all three indicators of mathematical reasoning ability but did not meet the indicators of mathematical manipulation. Then students with auditory learning styles met the four indicators of mathematical reasoning ability. Furthermore, students with kinesthetic learning styles also meet the four indicators of mathematical reasoning ability.